2020
DOI: 10.3390/cancers12113250
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circular RNAs in Pancreatic Ductal Adenocarcinoma and Biliary-Tract Cancers

Abstract: Pancreatic Ductal Adenocarcinoma (PDAC) and biliary-tract cancers (BTC) often present at a late stage, and consequently patients have poor survival-outcomes. Circular RNAs (circRNAs) are non-coding RNA molecules whose role in tumourigenesis has recently been realised. They are stable, conserved and abundant, with tissue-specific expression profiles. Therefore, significant interest has arisen in their use as potential biomarkers for PDAC and BTC. High-throughput methods and more advanced bioinformatic technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 141 publications
(212 reference statements)
1
24
0
Order By: Relevance
“…Over the last several years, although we should acknowledge that numerous efforts to improve the efficacy of surgery and chemotherapy in PAAD patients have been made, there are still few reliable biomarkers or effective therapeutic strategies for daily clinical practice in PAAD. Increasing evidence indicated that circRNAs have great potential to regulate cancer cell proliferation, apoptosis, invasion, EMT, metastasis and response to chemotherapy, implying that circRNAs may be used as novel potential therapeutic targets for treating various tumors including PAAD (9,10,21,22). Here, we confirmed that the knockdown of circ_0092314 suppressed the growth and invasion of PAAD cells in vitro, and resulted in reduced tumor size and tumor weight in vivo, suggesting that targeting circ_0092314 is a potential therapeutic strategy for PAAD.…”
Section: Discussionsupporting
confidence: 71%
“…Over the last several years, although we should acknowledge that numerous efforts to improve the efficacy of surgery and chemotherapy in PAAD patients have been made, there are still few reliable biomarkers or effective therapeutic strategies for daily clinical practice in PAAD. Increasing evidence indicated that circRNAs have great potential to regulate cancer cell proliferation, apoptosis, invasion, EMT, metastasis and response to chemotherapy, implying that circRNAs may be used as novel potential therapeutic targets for treating various tumors including PAAD (9,10,21,22). Here, we confirmed that the knockdown of circ_0092314 suppressed the growth and invasion of PAAD cells in vitro, and resulted in reduced tumor size and tumor weight in vivo, suggesting that targeting circ_0092314 is a potential therapeutic strategy for PAAD.…”
Section: Discussionsupporting
confidence: 71%
“…The altered expression of circRNAs between normal and pathological conditions has been observed in numerous diseases. 22 , 23 Therefore, circRNAs (especially in PBMCs) were selected to explore the possibility of being used as biomarkers for the diagnosis of these diseases.…”
Section: Biological Characteristics Of Circrnasmentioning
confidence: 99%
“…These features underline the requirement of developing more effective treatments for PaC. Noncoding RNAs (ncRNAs) are differentially expressed in cancer and control diverse signaling pathways involved in the regulation of therapeutic resistance [ 5 , 6 , 7 , 8 ]. An improved understanding of the relationship between therapeutic resistance and ncRNAs can provide meaningful insights to develop new treatment strategies for PaC.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study demonstrated that lncRNA-ADPGK-AS1 inhibits miR-205-5p, thereby promoting the progression of PaC via activating epithelial-to-mesenchymal transition (EMT) [ 13 ]. Moreover, circular RNAs (circRNAs) can control gene transcription via interaction with RNA-binding proteins [ 8 , 14 ]. They also regulate the signaling pathways through the sequestration of miRNAs [ 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation